Differences in the Bacterial Pattern of Patients with Histamine Intolerance Veränderte intestinale bakterielle Zusammensetzung bei Patienten mit Histaminintoleranz - Schink, Monic; Konturek, Peter C.; Tietz, Esther; Dieterich, Walburga; Neurath, Markus; Zopf, Yurdagül (Aktuelle Ernährungsmedizin, 2019)
Background Histamine intolerance (HIT) is a controversially discussed disorder. An impaired degradation of oral histamine intake due to diamine oxidase (DAO) deficiency is suggested as main cause, but other factors, including an altered gut flora, may also contribute to elevated histamine levels. We aimed to determine differences in the intestinal bacterial pattern of HIT-patients in comparison to healthy persons (HC). Material and methods All participants had a blood testing for total IgE, food-specific IgEs, TNF-α, plasma histamine and serum DAO activities. Stool samples were collected for analysis of stool histamine and zonulin levels. The bacterial composition of the stool samples was analysed by 16s rRNA sequencing using Illumina platform. Results A total of 18 participants (30.2±12.5yrs, 94,4% female) were included in the study, and categorized into HIT-patients (n=8, 28.9±11.2 yrs, 100% female) and healthy controls (n=10, 31.3±13.9yrs, 90% female). No significant differences in stool histamine levels were observed between groups, but HIT-patients showed tendentially increased levels of fecal zonulin. Microbiome analysis revealed a reduced bacterial diversity (p=0.05) and a higher abundance of Proteobacteria in the HIT-group. Additionally, HIT-patients showed a significantly decreased abundance of the butyrate-producing genera Faecalibacterium (p=0.045) and Butyricimonas (p=0.003) as well as lower proportions of Sutterella (p=0.043) and Hespellia (p=0.043). No increased numbers of known histamine-producing bacteria were detected in the study groups. Conclusion Our study results suggest an alteration of the microbial composition in HIT-patients. The higher abundance of Proteobacteria and lower abundance of butyrate-producing bacteria, as well as elevated stool zonulin levels indicate a dysbiosis and impaired intestinal barrier. However, an elevated histamine exposure due to gut bacteria may not be responsible for HIT pathogenesis.
CRIS-Team Scopus Importer:2019-11-05
Keywords: dysbiosis; histamine intolerance; intestinal barrier; microbiome